Chinese herbal medicine Dengzhan Shengmai capsule as adjunctive treatment for ischemic stroke: A systematic review and meta-analysis of randomized clinical trials. (February 2018) - Yang, Xiao-Ying; Wang, Li-Qiong; Li, Jin-Gen; Liang, Ning; Wang, Ying; Liu, Jian-Ping
Highlights: The effectiveness and safety of DZSM capsule for ischemic stroke was analysed. It appears that DZSM capsule can additionally improve neurological function, quality of life, and reduce recurrence rate based on conventional therapy for ischemic stroke. DZSM capsule seems to be safe forpatients with ischemic stroke. Majority of the included trials were of high or unclear risk of bias in methodological quality. More large, rigorous and adequately reported trials are needed to confirm positive findings. Abstract: Objective: The existing eligible randomized controlled trials (RCTs) were critically appraised for the effectiveness and safety of Chinese herbal medicine Dengzhan Shenmai for ischemic stroke. Design: Systematic review and meta-analysis (CRD42016042914, http://www.crd.york.ac.uk/PROSPERO). Methods: Six electronic databases were searched from inception to May 2016. Risk ratio (RR) and mean difference (MD) with a 95% confidence interval (CI) were used as effect estimates using RevMan 5.3. Meta-analysis was performed where data were available. A summary of finding table was generated by the GRADEpro (version 3.6). Results: We identified 14 RCTs involving 5206 participants. Majority of the included trials were of high risk of bias in methodological quality. For acute ischemic stroke, adding DZSM capsule to conventional therapy achieved higher Barthel Index scores (MD 22.37, 95% CI 21.34–23.40), lower neurological function deficit scores (MD – 3.73, 95% CI −5.27 to −2.19) and lower recurrence rate (RR 0.22, 95% CI 0.10, 0.46). For patients in their convalescence (or sequelae) stage of ischemic stroke, DZSM capsule was superior in improving quality of life (MD 28.8, 95% CI 7.10–50.50) and recurrence rate (RR 0.71, 95% CI 0.51–0.99) compared to placebo. No trials reported serious adverse events. Conclusion: DZSM capsule appears to improve neurological function, quality of life, and reduce recurrence rate based on conventional therapy for ischemic stroke. DZSM capsule seems generally safe for clinical application. However, the findings of benefit are inconclusive due to generally weak evidence, and further large, rigorous trials are still warranted.